The addition of radiotherapy to breast-conserving surgery improves survival for elderly patients with early breast cancer - Yang, Shi-Ping; Tan, Lu-Lu; Zhou, Ping; Lian, Chen-Lu; Wu, San-Gang; He, Zhen-Yu (Frontiers in Oncology, 2022)
Purpose To evaluate whether adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) was associated with better survival among elderly (≥70 years) breast cancer patients with T1-2N0 and estrogen receptor (ER) positive disease. Methods We included patients who met the inclusion criteria between 2010 and 2014 from the Surveillance, Epidemiology, and End Results program. Patients were subdivided into three groups based on surgery and RT: BCS alone, BCS plus RT, and refusal of RT. The primary outcomes were breast cancer-specific survival (BCSS) and overall survival (OS). Chi-squared tests, Kaplan–Meier method, and Multivariate Cox regression analysis were used for statistical analysis. Propensity score matching (PSM) was performed to minimize the potential selection bias. Results A total of 26586 patients were included in this analysis. The median follow-up was 66 months. Of these patients, 15591 (58.6%) patients received RT, RT was recommended but not performed due to patient refusal for 1270 (4.8%) patients, and RT was not recommended for 9725 (36.6%) patients. The 5-year BCSS was 98.3% for patients receiving RT, 97.1% for patients refusal of RT, and 96.4% for patients not recommended RT (P<0.001). The 5-year OS was 88.6% for patients receiving RT, 77.6% for patients who refused RT, and 72.1% for patients not recommended RT (P<0.001). Multivariate Cox regression analyses showed that patients who received adjuvant RT after BCS had significantly better BCSS (hazard ratio [HR] 0.523, 95%confidence interval [CI] 0.447-0.612, P<0.001) and OS (HR 0.589, 95%CI 0.558-0.622, P<0.001) compared to those without RT. A total of 7721 pairs of patients were matched successfully between those with and without RT using PSM. The results also showed that patients who received RT after BCS had significantly better BCSS (HR 562, 95%CI 0.467-0.676, P<0.001) and OS (HR 0.612, 95%CI 0.0.575-0.652, P<0.001) compared to those without RT. Conclusions These data suggest that individual counseling is important for treatment decision-making in elderly breast cancer patients with T1-2N0 and ER-positive disease. Given the relatively lower toxicity of modern RT techniques, adjuvant RT should be recommended in patients with high life expectancy.